All that really matters - Deese, Nicole (Bethany House, 2021)
"Molly McKenzie has made social media influencing a lucrative career, but nailing a TV show means proving she's as good in real life as she is online. So she volunteers with a youth program. Challenged at every turn by the program director, Silas, and the kids' struggles, she's surprised by her growing attachment. Has her perfect life been imperfectly built?"--